Numerical simulation of tornadogenesis - Grasso, Lewis D., author (Colorado State University. Libraries, 1992)
The CSU RAMS was used to investigate tornadogenesis using high resolution interactive nests to explicitly resolve the tornado. Convection was initiated with a warm bubble in a horizontally homogeneous environment using from a composite of soundings taken May 20, 1977, the day of the Del City tornado. The simulated supercell has many observed characteristics some of which are: a hook echo, bounded weak echo region, strong updrafts and a mesocyclone. The high resolution nests captured the necessary features that allowed tornadogenesis to occur. It is found that a pressure-deficit tube developed on the largest horizontal gradient of the updraft when the magnitude of the three dimensional vorticity exceeded the strain rate in this region. It is suggested that efficient tilting/convergence of vortex lines by the updraft gradient aided in allowing the vorticity term to exceed the strain term, in the diagnostic equation for pressure, and allow pressures to fall rapidly. Near cloud base and below, this tilting/convergence of vortex lines will locally be unable to allow the pressures to continue to fall at the base of the pressure-deficit tube since vertical motion is constrained to vanish at the lower boundary. The storm's downdrafts are thought to play a key role in reorientating vortex lines into a vertical position in the sub-cloud air. Convergence of sub-cloud air towards the pressure-deficit tube will also draw in already vertically orientated vortex lines. Once the vortex lines are converged sufficiently, the pressures will fall as the flow exhibits highly rotational characteristics, and allow the pressure-deficit tube to continue working towards the lower boundary. As the lower boundary is approached, increasing frictional forces will enhance the convergence of vortex lines.
May 15, 1992.
Also issued as author's thesis (M.S.) -- Colorado State University, 1992.
Keywords: Tornadoes; Tornadoes -- Mathematical models